'Fake food: authentic Japanese product'—On the rise of visuality in middlebrow Japanese culinary culture. Issue 2 (3rd April 2019) - Hopson, Nathan
Abstract: Food replicas ( shokuhin sanpuru ) line the show windows of cafes and restaurants in cities, towns, and villages throughout Japan. They are usually found artfully arranged in restaurant show windows or cases, facing and visible from the street, corridor, hall, etc., on which the restaurant is located. Building on consumers' familiarity with foods, ingredients, and cooking techniques, these replicas visually evoke other senses – taste, scent, texture, and mouthfeel – instantly providing massive amounts of information. As a ubiquitous visual marketing tool, sanpuru have contributed to the creation and maintenance of Japan's hybrid national culinary culture, especially the pervasive 'middlebrow' echelon of mainstream, everyday consumer culture. In particular, it is argued in this article that, as an inevitable, almost transparently naturalized part of the visual landscape of food and consumer culture, samples have played a crucial but underappreciated role in the establishment and dissemination of the much-remarked-on visual aesthetic of Japanese culinary culture.